Greening the work force in Brazilian hotels: The role of environmental training - Dias-Angelo, Fernanda; Jabbour, Charbel José Chiappetta [UNESP]; Calderaro, Jose Armando (Ios Press, 2014)
BACKGROUND: Organizations are increasingly required to reduce their environmental impact through the adoption of environmental management, which requires the support of human resource practices.OBJECTIVE: The objective of this study is to determine whether human resource management practices, especially training, are supporting environmental management practices at four hotels located in Brazil.METHODS: This research is qualitative, based on the analysis of four hotels in Brazil.RESULTS: Based on the systematized empirical evidence collected from four hotels (Hotels A, B, C, and D), it can be concluded that: (1) human resource management is still not fully aligned with environmental objectives at the hotels studied; (2) only Hotel B has implemented environmental management practices and aligned with human resource management in a more developed manner, which may indicate that these two variables of analysis could have interrelations; (3) environmental training as a human resource management practice was verified in all hotels analyzed.CONCLUSIONS: The greening of human resources practices is not fully aligned with environmental objectives in the hotels studied. If these hotels really wish to "go green," environmental training will be necessary. Hotel stakeholders play a major role in implementing the greening of the hotel industry.
Keywords: Green human resource management; sustainable human resources; training; environmental sustainability; hotels; service industry; Brazil; hospitality industry